Defective autophagosome trafficking contributes to impaired autophagic flux in coronary arterial myocytes lacking CD38 gene. (20th January 2014) - Zhang, Yang; Xu, Ming; Xia, Min; Li, Xiang; Boini, Krishna M.; Wang, Mi; Gulbins, Erich; Ratz, Paul H.; Li, Pin-Lan
Abstract: Aim: Autophagic flux is an important process during autophagy maturation in smooth muscle cells. However, the molecular mechanisms underlying autophagic flux in these cells are largely unknown. Here, we revealed a previously undefined role of CD38, an enzyme that metabolizes NADP + into NAADP, in the regulation of autophagic flux in coronary arterial myocytes (CAMs). Methods and results: In vivo CD38 gene knockout mice (CD38 −/− ) fed the high-fat Western diet showed increased accumulation of autophagosomes in coronary arterial media compared with that in wild-type (CD38 +/+ ) mice, suggesting that CD38 gene deletion results in a defective autophagic process in CAMs of coronary arteries. In primary cultured CAMs, CD38 gene deletion markedly enhanced 7-ketocholesterol (7-Ket, an atherogenic stimulus and autophagy inducer)-induced accumulation of autophagosomes and increased expression of an autophagic marker, LC3B. However, no difference in autophagosome formation was observed between CD38 +/+ and CD38 −/− CAMs when autophagic flux was blocked, which indicates that CD38 regulates autophagic flux rather than induction of autophagosome formation. Further, 7-Ket-induced formation of autophagolysosomes was markedly attenuated in CD38 −/− CAMs compared with CD38 +/+ CAMs. Mechanistically, CD38 gene deletion markedly inhibited 7-Ket-induced dynein activation and autophagosome trafficking, which were associated with attenuated lysosomal Ca 2+ release. Importantly, coronary arterial smooth muscle from CD38 −/− mice fed the Western diet exhibited phenotypic changes towards a more dedifferentiated state with abnormal extracellular matrix metabolism. Conclusion: Taken together, these results suggest that CD38 plays a critical role in autophagosome trafficking and fusion with lysosomes, thus controlling autophagic flux in CAMs under atherogenic stimulation.